Peningkatan Literasi Teknologi Mikrokontroler melalui Bimbingan Perakitan Kursi Pintar Berbasis ESP32 bagi Siswa SMPN 1 Tayu - Danang Hendrawan; Rizal Agri Wahyuadi; Muhammad Atiq; Raka Dian Mahardi; Sigit Prakosa A N; Dhandy Bagaskara (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2026)
This community service activity aims to enhance the technological literacy of junior high school students through structured guidance on assembling applied microcontroller systems. The program involved two students from SMPN 1 Tayu, Pati Regency, as activity partners. The implementation method consisted of several stages, including an introduction to the Arduino ecosystem, virtual circuit simulation using Wokwi, and hands-on practice in assembling and programming electronic components through the Arduino IDE. During the activity, students were guided to understand basic automation concepts, sensor functions, circuit connections, and simple programming logic. The main outcome was the successful development of a smart chair prototype designed to remind users about sitting duration by integrating a mechanical sensor and an audio module. Evaluation results showed that the guidance improved students' understanding of automation logic and strengthened their practical skills in applying microcontroller technology. In addition, the activity encouraged students to develop creativity, problem-solving abilities, and interest in applied technology. Overall, this program had a positive impact by promoting health-oriented technological innovation within the school environment.